Tanggung Jawab Puskesmas atas Pemberian Vitamin Kadaluwarsa kepada Pasien Ditinjau dari Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016 Tentang Standar Pelayanan Kefarmasian di Puskesmas Jo. Buku III KUHPerdata - Fikri Fadhil Jaenuddin; Sri Ratna Suminar (Bandung Conference Series: Law Studies, 2022)
Abstract. In puskesmas there are pharmaceutical services that include drug management and clinical pharmacy services. One of the efforts to strengthen health facilities, requires health workers including pharmacists and pharmacy in charge of health centers to have the ability to organize health services according to standards. Pharmacists as the person in charge of pharmaceutical services in puskesmas must carry out pharmaceutical services in accordance with standards in order to improve the quality of service and patient safety. In 2019 there were events carried out by Health Center (Pharmacist) officers in giving drugs to patients. A pregnant woman named Novi aged (21) in Penjaringan, North Jakarta was given expired vitamins when checking the contents at Kamal Muara Health Center, Penjaringan. In the vitamin B6 wrap for fetal boosters, there is an expired statement in April 2019 that has been crossed out. The purpose of this study is the known classification of pharmacists' actions on the provision of expired vitamins to patients when viewed from Book III of the Civil Code. And the known responsibility of puskesmas to patients for the provision of expired vitamins is reviewed from the Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016 concerning Standards of Pharmaceutical Services in Puskesmas Jo. Buku III KUHPerdata. The method of approach used is normative juridical, the research specifications in this research are descriptive analytical, data collection techniques in this research literature study as well as analytical methods in this study using qualitativ analysis methods. Then it was obtained the result that there was an omission committed by the Pharmacist. Pharmacist's actions included in unlawful acts and health centers must be responsible for the actions of the pharmacist. Abstrak. Di Puskesmas terdapat pelayanan kefarmasian yang mencakup pengelolaan obat dan pelayanan farmasi klinik. Salah satu upaya penguatan fasilitas kesehatan ini, menuntut tenaga kesehatan termasuk Apoteker dan penanggung jawab farmasi di Puskesmas untuk memiliki kemampuan dalam menyelenggarakan pelayanan kesehatan sesuai standar. Apoteker sebagai penanggung jawab pelayanan kefarmasian di Puskesmas wajib melaksanakan pelayanan kefarmasian sesuai standar dalam rangka peningkatan mutu pelayanan dan keselamatan pasien. Pada tahun 2019 terdapat peristiwa yang dilakukan petugas Puskesmas (Apoteker) dalam memberikan obat kepada pasien. Seorang ibu hamil bernama Novi berumur (21) di Penjaringan, Jakarta Utara diberikan vitamin kedaluwarsa saat memeriksakan kandungan di Puskesmas Kamal Muara, Penjaringan. Dalam bungkus vitamin B6 untuk penguat janin itu, ada keterangan kedaluwarsa pada April 2019 yang telah dicoret. Tujuan penelitian ini adalah Diketahuinya klasifikasi perbuatan Apoteker atas pemberian vitamin kadaluwarsa kepada pasien jika ditinjau dari Buku III KUHPerdata. Serta Diketahuinya tanggung jawab Puskesmas kepada pasien atas pemberian vitamin kadaluwarsa ditinjau dari Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016 Tentang Standar Pelayanan Kerfarmasian di Puskesmas Jo. Buku III KUHPerdata. Metode pendekatan yang digunakan adalah yuridis normatif, spesifikasi penelitian dalam penelitian ini bersifat deskriptif analitis, Teknik pengumpulan data dalam penelitian ini studi kepustakaan serta metode analisis dalam penelitian ini menggunakan metode analisis kualitatif. Kemudian diperoleh hasil bahwa adanya suatu kelalaian yang dilakukan oleh Apoteker. Perbuatan Apoteker termasuk kedalam perbuatan melawan hukum serta puskesmas harus bertanggung jawab atas perbuatan apoteker tersebut.